Service quality antecedents and their relationship with repurchase intention in the Singapore low-cost carrier market. - Goh, Dian Yang. (2011)
A quantitative methodology was employed in presenting LCC consumers with an extensive 38-question questionnaire, the results of which uncovered the relationship between such antecedents as the quality of in-flight meals, quality of cabin crew’s service standard, flight punctuality, service recovery standard, and consumer satisfaction, as well as the relationship between consumer satisfaction and repurchase intention. The results of the data analysis allow us to rank the antecedents in terms of relative importance, as reflected in the magnitude of correlation with consumer satisfaction, and then recommend particular attention to those antecedents of higher ranking. Acknowledgment of the study accounting for a substantial but not overwhelming amount of the variation in consumer satisfaction indicates the presence of to-be-determined alternative factors at play – our study serves as meaningful bedrock upon which future studies of the consumer experience with LCCs in Singapore can stand.